Developmental control of glucosamine and galactosamine levels during conidation in Neurospora crassa. - Schmit, J C (1975)
The glucosamine and galactosamine content of mycelia was measured in cultures of Neurospora crassa grown on the surface of dialysis membranes. The glucosamine content was relatively constant throughout the different regions of the mycelial mat. The galactosamine content, however, was always lower in the growing-front region of the mycelial mat than in the older regions. At most, only low levels of galactosamine were necessary for the formation of hyphae at the growing front of a mycelial mat. Thus, galactosamine-containing polymers cannot be a major shape-determining component of the cell walls of these hyphae in Neurospora. The effect of conidiation on the amino sugar content was determined by using the bd (band) strain of N. crassa. When grown on the surface of dialysis membranes, this strain rhythmically produced regions of conidiating and non-conidiating growth. With this strain, it was concluded that conidiation did not affect the amino sugar levels. Since conidia that contained only very low levels of galactosamine were produced from regions of the mycelial mat that contained much higher levels of this amino sugar, there must be some mechanism of spatial differentiation that prevented the accumulation of galactosamine-containing polymers in conidia.